Deep neural networks for multimodal imaging and biomedical applications - Suresh, Annamalai, 1977-; Udendran, R., 1992-; Vimal, S., 1984- (Advances in bioinformatics and biomedical engineering book series., 2020)
"This book provides research exploring the theoretical and practical aspects of emerging data computing methods and imaging techniques within healthcare and biomedicine. The publication provides a complete set of information in a single module starting from developing deep neural networks to predicting disease by employing multi-modal imaging"--